Освоение инновационных форм обучения в рамках программы повышения квалификации для преподавателей педагогических специальностей РИПКСО - Бекмагамбетова, М.Ж.; Бекмагамбетов, Р.К. (My University, 2016)
The article describes the process of development of innovative forms of learning within the training programs for teachers and pedagogical skills Republican institute for development of leading and research-pedagogical staff of education system their effectiveness in practice.
Keywords: training; online training; self-development of technology; self-improvement; self- realization; the digital technology; the system of evaluation